PENINGKATAN KOMPETENSI ANALISIS DATA KUANTITATIF PADA MAHASISWA DENGAN MODEL PEMBELAJARAN KOOPERATIF JIGSAW II - Wijaya Heru Santosa (CARAKA, 2018)
This study aimed to describe the use / application of Jigsaw II cooperative learning in enhancing the ability of quantitative data analysis courses students of educational research 5th semester, Indonesian Language and Literature Teaching, FKIP, Universitas Sarjanawiyata Tamansiswa Yogyakarta. Data action type of cooperative learning of Jigsaw II is collected by observation. Data on the student's ability quantitative analysis of the data collected by the testing techniques. Student response data on cooperative learning of Jigsaw II is collected by interview. The analyzed data is qualitative data is data from the learning process of planning, action, reflection to assign actions I. Based on the results of research and discussion since the first cycle to cycle dengan III can be concluded that cooperative learning of Jigsaw model II (1) improve the ability to apply the formula of quantitative analysis in the course of educational research. Increased ability proved that (a) the competence of the central tendency meenerapkan formula of 60%, 75% to 90%; (B) the competence to apply the formula of correlation analysis with a standard deviation of 72%, 84%, to 84%; (C) the competence to apply the formula of correlation analysis with a deviation of 40%, 66%, to 85%; (D) the competence to apply the formula of correlation analysis with the original data of 40%, 68%, to 88%; € competencies and comparative analysis with t test of 56%, 64% to 80%. (2) can improve the quality of learning characterized by increasingly effective student learning time with the group and the more effective in assessing the quality of the students themselves